A method for preparing pectin hydrogel with high mechanical strength
By introducing metal coordination bonds and boron oxygen bonds into pectin hydrogels, physical-chemical bonds are synergistically crosslinked, the problem of insufficient mechanical properties of pectin hydrogels in the prior art is solved, and its tensile strength and tensile properties are significantly improved, and the preparation process is simplified, which is suitable for large-scale production.
Patent Information
- Application Number
- CN202210777103.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-04
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-07-04
AI Technical Summary
The prior art is difficult to significantly improve the mechanical properties of pectin hydrogels through simple and fast methods, resulting in limited applications in fields such as smart coatings, flexible sensing and biomedicine.
By introducing metal coordination bonds and boron oxygen bonds into the pectin hydrogel, the hydroxyl groups on the pectin molecular chain form a reinforced bond with the borate to achieve synergistic crosslinking of physical-chemical bonds, thereby improving the mechanical properties of the pectin hydrogel. The specific method includes adding pectin powder to the borax solution and stirring to form a viscous mixed solution, and then immersing it in the divalent metal ion solution.
The mechanical properties of pectin hydrogel have been significantly improved, the tensile strength has been improved by 4 times, and it has good tensile properties. It has a wide range of materials, and the preparation process is simple and fast, and it is easy to produce on a large scale.
Smart Images

Figure CN114989456B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of gel materials, and particularly relates to a method for preparing pectin hydrogel with high mechanical strength. Background Art
[0002] Pectin hydrogel has great application potential in smart coatings, flexible sensors and biomedicine due to its good conductivity, tunability and biocompatibility. However, the defects of the pectin hydrogel network seriously weaken its mechanical properties and limit its application. At present, researchers have used many methods to improve the mechanical properties of pectin hydrogel, but all of them have one or more shortcomings: such as complex preparation process and limited enhancement effect. Improving the mechanical properties of pectin hydrogel by simple and fast methods is still a challenge.
[0003] In general, the introduction of strong cross-linking bonds will increase the cross-linking density of the gel molecular network, thereby improving the mechanical properties of the gel. In the pectin system, by introducing divalent metal ions to form physical cross-links with the gel network, the mechanical properties of the hydrogel can be improved to a certain extent (Celus, et al., Comprehensive Reviews in Food Science and Food Safety 2018, 17, 1576-1594). However, divalent metal ions usually only act on the carboxyl groups on the pectin molecular chains, and because of the different degrees of methylation on the pectin molecular chains, the strategy of cross-linking divalent metal ions to improve the mechanical properties of the gel is greatly limited. In addition, in recent years, the method of enhancing the mechanical properties of gels by binary network composite cross-linking has been widely used by researchers. In 2020, Wu's research group prepared a double network hydrogel by compounding pectin with polyacrylamide (Wu, et al., International Journal of Biological Macromolecules 2020, 149, 707-716), which has strong mechanical properties. However, the process of constructing a hydrogel double network is complicated, and a quick and simple method to improve the mechanical properties of pectin hydrogels has not yet been achieved.
[0004] It can be seen that it is crucial to develop a new strategy to improve the mechanical properties of pectin hydrogels. Summary of the invention
[0005] In view of the above-mentioned performance defects of pectin hydrogel, the present invention provides a simple and rapid method for preparing pectin hydrogel with high mechanical strength, thereby solving the technical problem that the prior art cannot effectively improve the mechanical properties of pectin hydrogel.
[0006] A method for preparing a pectin hydrogel with high mechanical strength, characterized in that the hydrogel is prepared by the following method:
[0007] Dissolve borax in deionized water and stir with a magnetic stirrer; after the borax is completely dissolved, add pectin powder to the dissolved borax solution and continue stirring until the pectin powder is dissolved to form a viscous mixed solution. Pour the above viscous mixed solution into a glass dish, spread it flat, place it in a 60°C oven to dry for 2 to 3 hours, and then move it to room temperature to continue drying for 8 to 12 hours to obtain a pectin hydrogel film; finally, immerse the obtained pectin hydrogel film in a divalent metal ion solution for 5 to 20 minutes to finally obtain a pectin hydrogel with high mechanical strength.
[0008] The pectin is pectin with galacturonic acid (on a dry basis) ≥ 74.0% and an esterification degree of 55%.
[0009] The borax is sodium tetraborate decahydrate.
[0010] The mass percentage of the borax in the mixed solution is 0.2wt% to 0.6wt%.
[0011] The mass percentage of the pectin in the mixed solution is 2wt% to 3wt%.
[0012] The divalent metal ion solution is Zn 2+ , Cu 2+ , Ca 2+ and Fe 2+ Salt solution, concentration is 0.05mol / L~0.3mol / L.
[0013] Compared with the prior art, the present invention has the following advantages:
[0014] 1. The present invention simultaneously introduces metal coordination bonds and boron-oxygen bonds into the pectin hydrogel network. As a strong physical bond, the metal coordination bond gives the pectin hydrogel high dynamic properties. Moreover, compared with the traditional pectin-metal ion system, the present invention makes full use of the characteristics of the hydroxyl groups on the pectin molecular chain and the borate radical to form a strong chemical bond (boron-oxygen bond), and finally achieves a significant improvement in the mechanical properties of the pectin hydrogel through physical-chemical bond synergistic crosslinking.
[0015] from Figure 1 It can be seen that compared with the original pectin gel, the tensile strength of the high mechanical strength pectin hydrogel disclosed in the present invention is increased by 4 times. Figure 2 This is a tensile test diagram of pectin hydrogel. It can be clearly seen from the figure that the high mechanical strength pectin hydrogel disclosed in the present invention has good tensile properties.
[0016] 2. The materials used in the present invention are widely available, and the preparation process is simple and rapid, and it is easy to realize large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a stress-strain curve of the high mechanical strength pectin hydrogel disclosed in the present invention
[0018] Figure 2 This is a tensile test diagram of the high mechanical strength pectin hydrogel disclosed in the present invention DETAILED DESCRIPTION
[0019] Embodiment 1 A method for preparing a pectin hydrogel with high mechanical strength comprises the following steps:
[0020] Dissolve 0.6g of sodium tetraborate decahydrate in 100mL of deionized water and stir with a magnetic stirrer. After the sodium tetraborate decahydrate is completely dissolved, add 3.0g of pectin powder to the sodium tetraborate decahydrate solution and continue stirring until the pectin powder is dissolved to form a viscous mixed solution. Pour the above viscous mixed solution into a glass dish and flatten it. Place it in a 60°C oven and dry it for 3h, then move it to room temperature and continue drying for 12h to obtain a pectin hydrogel film. The prepared pectin hydrogel film was immersed in a zinc acetate solution with a concentration of 0.3mol / L for 20min, and finally a pectin hydrogel with high mechanical strength was obtained. The maximum tensile strength of the prepared pectin hydrogel is 1.21MPa.
[0021] Comparative Example 1: Dissolve 1g of sodium tetraborate decahydrate in 100mL of deionized water and stir with a magnetic stirrer. After the sodium tetraborate decahydrate is completely dissolved, add 3.0g of pectin powder to the sodium tetraborate decahydrate solution and continue stirring until the pectin powder is dissolved to form a viscous mixed solution. Pour the above viscous mixed solution into a glass dish and flatten it. Place it in a 60°C oven and dry it for 1.5h, then move it to room temperature and continue drying for 12h to obtain a pectin hydrogel film. The obtained pectin hydrogel film is immersed in a zinc acetate solution with a concentration of 0.3mol / L for 20min, and finally a pectin hydrogel with high mechanical strength is obtained. The maximum tensile strength of the prepared pectin hydrogel is 0.8MPa.
[0022] Embodiment 2 A method for preparing a pectin hydrogel with high mechanical strength comprises the following steps:
[0023] Dissolve 0.6g of sodium tetraborate decahydrate in 100mL of deionized water and stir with a magnetic stirrer. After the sodium tetraborate decahydrate is completely dissolved, add 3.0g of pectin powder to the sodium tetraborate decahydrate solution and continue stirring until the pectin powder is dissolved to form a viscous mixed solution. Pour the above viscous mixed solution into a glass dish and flatten it. Place it in a 60°C oven and dry it for 3h, then move it to room temperature and continue drying for 8h to obtain a pectin hydrogel film. The prepared pectin hydrogel film was immersed in a zinc acetate solution with a concentration of 0.1mol / L for 15min, and finally a pectin hydrogel with high mechanical strength was obtained. The maximum tensile strength of the prepared pectin hydrogel is 0.79MPa.
[0024] Comparative Example 2: Dissolve 0.1g of sodium tetraborate decahydrate in 100mL of deionized water and stir with a magnetic stirrer. After the sodium tetraborate decahydrate is completely dissolved, add 3.0g of pectin powder to the sodium tetraborate decahydrate solution and continue stirring until the pectin powder is dissolved to form a viscous mixed solution. Pour the above viscous mixed solution into a glass dish and flatten it. Place it in a 60°C oven and dry it for 3h, then move it to room temperature and continue drying for 6h to obtain a pectin hydrogel film. The obtained pectin hydrogel film is immersed in a zinc acetate solution with a concentration of 0.1mol / L for 15min, and finally a pectin hydrogel with high mechanical strength is obtained. The maximum tensile strength of the prepared pectin hydrogel is 0.62MPa.
[0025] Example 3 A method for preparing a pectin hydrogel with high mechanical strength comprises the following steps:
[0026] Dissolve 0.4g of sodium tetraborate decahydrate in 100mL of deionized water and stir with a magnetic stirrer. After the sodium tetraborate decahydrate is completely dissolved, add 3.0g of pectin powder to the sodium tetraborate decahydrate solution and continue stirring until the pectin powder is dissolved to form a viscous mixed solution. Pour the above viscous mixed solution into a glass dish and flatten it. Place it in a 60℃ oven and dry it for 2h, then move it to room temperature and continue drying for 12h to obtain a pectin hydrogel film. The prepared pectin hydrogel film was immersed in a zinc acetate solution with a concentration of 0.3mol / L for 20min, and finally a pectin hydrogel with high mechanical strength was obtained. The maximum tensile strength of the prepared pectin hydrogel is 0.58MPa.
[0027] Comparative Example 3: Dissolve 0.4 g of sodium tetraborate decahydrate in 100 mL of deionized water and stir with a magnetic stirrer. After the sodium tetraborate decahydrate is completely dissolved, add 1.5 g of pectin powder to the sodium tetraborate decahydrate solution and continue stirring until the pectin powder is dissolved to form a viscous mixed solution. Pour the above viscous mixed solution into a glass dish and flatten it. Place it in a 60°C oven and dry it for 2 hours, then move it to room temperature and continue drying for 14 hours to obtain a pectin hydrogel film. The obtained pectin hydrogel film is immersed in a zinc acetate solution with a concentration of 0.3 mol / L for 20 minutes, and finally a pectin hydrogel with high mechanical strength is obtained. The maximum tensile strength of the prepared pectin hydrogel is 0.49 MPa.
[0028] Example 4 A method for preparing a pectin hydrogel with high mechanical strength comprises the following steps:
[0029] Dissolve 0.2g of sodium tetraborate decahydrate in 100mL of deionized water and stir with a magnetic stirrer. After the sodium tetraborate decahydrate is completely dissolved, add 2.0g of pectin powder to the sodium tetraborate decahydrate solution and continue stirring until the pectin powder is dissolved to form a viscous mixed solution. Pour the above viscous mixed solution into a glass dish and flatten it. Place it in a 60°C oven and dry it for 3h, then move it to room temperature and continue drying for 12h to obtain a pectin hydrogel film. The prepared pectin hydrogel film was immersed in a zinc acetate solution with a concentration of 0.05mol / L for 20min, and finally a pectin hydrogel with high mechanical strength was obtained. The maximum tensile strength of the prepared pectin hydrogel is 0.29MPa.
[0030] Comparative Example 4: Dissolve 0.2 g of sodium tetraborate decahydrate in 100 mL of deionized water and stir with a magnetic stirrer. After the sodium tetraborate decahydrate is completely dissolved, add 2.0 g of pectin powder to the sodium tetraborate decahydrate solution and continue stirring until the pectin powder is dissolved to form a viscous mixed solution. Pour the above viscous mixed solution into a glass dish and flatten it. Place it in a 60°C oven and dry it for 3 hours, then move it to room temperature and continue drying for 12 hours to obtain a pectin hydrogel film. The obtained pectin hydrogel film is immersed in a zinc acetate solution with a concentration of 0.01 mol / L for 25 minutes, and finally a pectin hydrogel with high mechanical strength is obtained. The maximum tensile strength of the prepared pectin hydrogel is 0.15 MPa.
[0031] Example 5 A method for preparing a pectin hydrogel with high mechanical strength comprises the following steps:
[0032] Dissolve 0.2g of sodium tetraborate decahydrate in 100mL of deionized water and stir with a magnetic stirrer. After the sodium tetraborate decahydrate is completely dissolved, add 2.0g of pectin powder to the sodium tetraborate decahydrate solution and continue stirring until the pectin powder is dissolved to form a viscous mixed solution. Pour the above viscous mixed solution into a glass dish and flatten it. Place it in a 60°C oven and dry it for 3h, then move it to room temperature and continue drying for 8h to obtain a pectin hydrogel film. The prepared pectin hydrogel film is immersed in a calcium chloride solution with a concentration of 0.3mol / L for 10min, and finally a pectin hydrogel with high mechanical strength is obtained. The maximum tensile strength of the prepared pectin hydrogel is 0.25MPa.
[0033] Comparative Example 5: Dissolve 0.2g of sodium tetraborate decahydrate in 100mL of deionized water and stir with a magnetic stirrer. After the sodium tetraborate decahydrate is completely dissolved, add 2.0g of pectin powder to the sodium tetraborate decahydrate solution and continue stirring until the pectin powder is dissolved to form a viscous mixed solution. Pour the above viscous mixed solution into a glass dish and flatten it. Place it in a 60°C oven and dry it for 3h, then move it to room temperature and continue drying for 8h to obtain a pectin hydrogel film. The obtained pectin hydrogel film is immersed in a magnesium chloride solution with a concentration of 0.5mol / L for 10min, and finally a pectin hydrogel with high mechanical strength is obtained. The maximum tensile strength of the prepared pectin hydrogel is 0.2MPa.
[0034] Example 6 A method for preparing a pectin hydrogel with high mechanical strength comprises the following steps:
[0035] Dissolve 0.4g of sodium tetraborate decahydrate in 100mL of deionized water and stir with a magnetic stirrer. After the sodium tetraborate decahydrate is completely dissolved, add 2.5g of pectin powder to the sodium tetraborate decahydrate solution and continue stirring until the pectin powder is dissolved to form a viscous mixed solution. Pour the above viscous mixed solution into a glass dish and flatten it. Place it in a 60°C oven and dry it for 3h, then move it to room temperature and continue drying for 10h to obtain a pectin hydrogel film. The prepared pectin hydrogel film is immersed in a 0.2mol / L ferric chloride solution for 10min, and finally a pectin hydrogel with high mechanical strength is obtained. The maximum tensile strength of the prepared pectin hydrogel is 0.34MPa.
[0036] Comparative Example 6: 0.4 g of sodium tetraborate decahydrate was dissolved in 100 mL of deionized water and stirred with a magnetic stirrer. After the sodium tetraborate decahydrate was completely dissolved, 2.5 g of pectin powder (esterification degree of 65%) was added to the sodium tetraborate decahydrate solution and stirred until the pectin powder was dissolved to form a viscous mixed solution. The viscous mixed solution was poured into a glass dish and flattened, placed in a 60°C oven and dried for 3 hours, and then moved to room temperature and continued to dry for 10 hours to obtain a pectin hydrogel film. The obtained pectin hydrogel film was immersed in a 0.2 mol / L ferric chloride solution for 3 minutes, and finally a pectin hydrogel with high mechanical strength was obtained. The maximum tensile strength of the prepared pectin hydrogel was 0.27 MPa.
[0037] Example 7 A method for preparing a pectin hydrogel with high mechanical strength comprises the following steps:
[0038] Dissolve 0.6g of sodium tetraborate decahydrate in 100mL of deionized water and stir with a magnetic stirrer. After the sodium tetraborate decahydrate is completely dissolved, add 2.0g of pectin powder to the sodium tetraborate decahydrate solution and continue stirring until the pectin powder is dissolved to form a viscous mixed solution. Pour the above viscous mixed solution into a glass dish and flatten it. Place it in a 60°C oven and dry it for 2.5h, then move it to room temperature and continue drying for 12h to obtain a pectin hydrogel film. The prepared pectin hydrogel film was immersed in a copper sulfate solution with a concentration of 0.1mol / L for 15min, and finally a pectin hydrogel with high mechanical strength was obtained. The maximum tensile strength of the prepared pectin hydrogel is 0.49MPa.
[0039] Comparative Example 7: Dissolve 0.6g of sodium tetraborate in 100mL of deionized water and stir with a magnetic stirrer. After the sodium tetraborate is completely dissolved, add 2.0g of pectin powder to the sodium tetraborate solution and continue stirring until the pectin powder is dissolved to form a viscous mixed solution. Pour the above viscous mixed solution into a glass dish and flatten it. Place it in a 60°C oven and dry it for 4 hours, then move it to room temperature and continue drying for 12 hours to obtain a pectin hydrogel film. The prepared pectin hydrogel film is immersed in a copper sulfate solution with a concentration of 0.1mol / L for 15min, and finally a pectin hydrogel with high mechanical strength is obtained. The maximum tensile strength of the prepared pectin hydrogel is 0.41MPa.
Claims
1. A method for preparing a high mechanical strength pectin hydrogel, characterized in that The hydrogel is prepared by the following method: Dissolve borax in deionized water and stir with a magnetic stirrer; after the borax is completely dissolved, add pectin powder to the dissolved borax solution, continue stirring until the pectin powder is dissolved to form a viscous mixed solution, pour the viscous mixed solution into a glass dish, spread it flat, place it in a 60°C oven to dry for 2 to 3 hours, and then move it to room temperature to continue drying for 8 to 12 hours to obtain a pectin hydrogel film; finally, immerse the prepared pectin hydrogel film in a divalent metal ion solution for 5 to 20 minutes to finally obtain a pectin hydrogel with high mechanical strength.
2. The method for preparing the hydrogel according to claim 1, characterized in that The pectin powder is pectin powder with galacturonic acid content of ≥74.0% on a dry basis and an esterification degree of 55%.
3. The method for preparing the hydrogel according to claim 1, characterized in that The borax is sodium tetraborate decahydrate.
4. The method for preparing the hydrogel according to claim 1, characterized in that The mass percentage of the borax in the mixed solution is 0.2wt% to 0.6wt%.
5. The method for preparing the hydrogel according to claim 1, characterized in that The mass percentage of the pectin in the mixed solution is 2wt% to 3wt%.
6. The method for preparing the hydrogel according to claim 1, characterized in that The divalent metal ion solution is Zn 2+ , Cu 2+ , Ca 2+ and Fe 2+ Salt solution, concentration is 0.05mol / L~0.3mol / L.
Citation Information
Patent Citations
Hemostatic dressing
US20120282320A1